P2 IMPACT OF CATHETER ABLATION ON ARRHYTHMIC STORM: A SINGLE–CENTER EXPERIENCE. (18th May 2022) - Cutolo, A; Bellin, A; Antonucci, A; Cavalli, G; China, P; Quinto, L; Vitale, R; Themistoclakis, S
Abstract: Background: Arrhythmic storm (AS) is a medical emergency whom management is multidisciplinary and includes antiarrhythmic medications, sedation and mechanical circulatory support, as well as catheter ablation, a procedure that is gaining growing relevance in clinical practice, supported by guidelines. Methods and Aims: It is a retrospective observational study of patients admitted to Cardiology Department of Ospedale dell'Angelo for AS from 2016 to 2021. The primary endpoint was the rate of arrhythmic recurrences and their clinical predictors; the secondary endpoint was a composite of all– cause death, LVAD or cardiac transplant. Successful CA was defined as no inducibility of any VT at the end of the procedure. Result: We evaluated 74 patients. Catheter ablation (CA) was performed in 56 patients, while in the other 18 patients, the treatment of the arrhythmic emergency was limited to medical therapy. At a median follow–up of 10 months (range 4–36 months), the overall arrhythmic recurrence rate was 39.1% and AS recurrence occurred in 11% of patients; the incidence of the composite end–point of all–cause death, LVAD implant or cardiac transplant was 20.2%. B–blockers (85% vs 100%, p = 0.025) and successful CA (60% vs 88.6%, p = 0.021) were associated with less arrhythmic recurrences. At multivariate analysis, a successful CA was an independent predictor of arrhythmic recurrence free survival (HR 0.32, [0.11–0.94], p = 0.039), and of ICD shocks free survival (HR 0.087, [0.02–0.37], p = 0.001). ICD shocks at admission (8.06 ± 9.8 vs 3.18 ± 4.24, p = 0.005), NYHA class III–IV (46.6% vs 5%, p = 0.001), medical treatment (53.3% vs 83%, p = 0.031), ICD shocks during follow–up (53.3% vs 18, 6%, p = 0.004) and AS recurrence (33.3% vs 10.1%, p = 0.039) were associated with an increased rate of the secondary endpoint. Conclusions: In our real world experience of patients admitted for AS, CA was a predictor of arrhythmic recurrence free survival and may have a role in improving quality of life and prognosis by reducing ICD shocks. CA was an independent predictor of the reduced incidence of all–cause death, LVAD implant or cardiac transplant, although this finding might reflect a more severe cardiac disease of the medically treated patients than a real benefit of CA on mortality.